Studi Morfometrik Dan Meristik Ikan Kurisi (Nemipterus Sp) Yang Didaratkan Di Pelabuhan Perikanan Nusantara (PPN) Sungailiat Kabupaten Bangka - Andi Gustomi; Sri Dewi Dinata Putri (Journal of Tropical Marine Science, 2019)
Curry fish (Nemipterus sp) is one of the fish which is the main commodity of various fish Landed In Nusantara Fishery Harbour Of Sungailiat, Bangka Regency.This Curry fish is used as a side dish. The Study Of Morfometric and Meristic Studies of Curry Fish (Nemipterus sp) Landed In Nusantara Fishery Harbour Of Sungailiat, Bangka Regency. The research was held on December 2018 to January 2019 in Nusantara Fishery Harbour (PPN) Of Sungailiat, Bangka Regency. The data was taken using random sampling method. This research takes 23 morfometric characters and 9 meristic characters to analyze.The morphometric character of Curry Fish showed that total length is 16,5 cm to 21 cm with average 18,93 cm. The character of merictic of Curry Fish has the formula of Dorsal rays (D.XI-D.XII.8), Anal rays (A.III.11-A.III.14), Sirip Dada (P..12), Sirip Perut (V.9-V.10) dan Caudal rays (C.40-C.43). Based on identification Curry Fish is from genus of Nemipterus with Species Nemipterus japonicus.